An analysis of different therapeutic options in patients with Cushing's syndrome due to bilateral macronodular adrenal hyperplasia: a single‐centre experience. (27th March 2015) - Albiger, N.M.; Ceccato, F.; Zilio, M.; Barbot, M.; Occhi, G.; Rizzati, S.; Fassina, A.; Mantero, F.; Boscaro, M.; Iacobone, M.; Scaroni, C.
Summary Context Bilateral macronodular adrenal hyperplasia (BMAH) is a rare form of Cushing's syndrome (CS). A variety of in vivo tests to identify aberrant receptor expression have been proposed to guide medical treatment. Unilateral adrenalectomy (UA) may be effective in selected patients, but little is known about recurrence during follow‐up. Objective To describe a series of patients with BMAH and CS treated by different approaches, with a particular focus on the benefit of UA. Design and patients We retrospectively assessed 16 patients with BMAH and CS (11 females, five males), analysing the in vivo cortisol response to different provocative tests. Twelve of the 16 patients underwent UA and were monitored over the long term. Results Based on in vivo test results, octreotide LAR or propranolol was administered in one case of food‐dependent CS and two patients with a positive postural test. A significant improvement in biochemical values was seen in all patients but with limited clinical response. UA was performed in 12 patients, producing long‐term remission in three (106 ± 28 months; range: 80–135), recurrence in eight (after 54 ± 56 months; range 12–180) and persistence in one other. Four patients subsequently underwent contralateral adrenalectomy for overt CS, one received ketoconazole, and four other patients remain under observation for subclinical CS. Conclusions Medical treatment based on cortisol response to provocative tests had a limited role in our patients, whereas UA was useful in some of them. Although recurrence is likely, the timing of onset is variable and close follow‐up is mandatory to identify it.